Monitoramento de armazenagem de grãos em silos utilizando o sensor Micropilot FMR67 e o ambiente de automação Tia Portal - SILVA, Karine Brito da (2024)
This work presents a project that uses the Micropilot FMR67 level sensor - a free wave radar - for continuous measurement of bulk solids inside storage silos, providing reliable and accurate data. The proposed system is controlled by a Programmable Logic Controller (PLC), which plays a crucial role in managing the data received by the sensor and in volume monitoring. The data collected and processed by the PLC is displayed on a Human Machine Interface (HMI), which allows the operator to monitor the silo level in real time. This not only helps you quickly identify and resolve problems, but also provides a solid foundation for continuous process improvement. The implementation of this system brings several significant benefits to the company, as the automation of storage monitoring increases operational efficiency, reduces the time and effort required for these activities and minimizes the risks associated with manual intervention.